Carbons derived from alcohol-treated bacterial cellulose with optimal porosity for Li–O2 batteries. (November 2021) - Wang, Wenhai; Khabazian, Siavash; Roig-Sanchez, Soledad; Laromaine, Anna; Roig, Anna; Tonti, Dino
Abstract: Porous carbons are important cathode materials for metal-air batteries, but the most usual methods to prepare these porous structures are complex and of high cost. We have prepared porous carbons from bacterial cellulose (BC) hydrogels by a simple water-alcohol solvent exchange before carbonization. Alcohol treatment facilitates looser and more open structures than untreated BC, resulting in porous carbon structures with high surface area, appropriate for electrochemical applications. Used as cathodes in lithium-oxygen batteries, the carbon derived from 1-butanol treated BC has excellent discharge capacity (5.6 mA h cm −2 ) and good cycle life. This work presents a sustainable, straightforward and fast way to prepare porous carbon materials from BC. Graphical abstract: Image 1 Highlights: Highly porous carbons obtained by pyrolysis of bacterial cellulose alcohol hydrogels. Morphology evolution reveals presence of liquid pyrolysis intermediates. Remarkable performance of carbon from butanol-treated cellulose in Li–O2 batteries.